Synthesis, structural, and optical properties of type-II ZnO–ZnS core–shell nanostructure - Sookhakian, M.; Amin, Yusoff Mohd; Basirun, Wan Jefrey; Tajabadi, M.T.; Kamarulzaman, N. (Elsevier, 2014)
We demonstrate a facile one-step method for the preparation of ZnO–ZnS core–shell type-II nanostructures, pure ZnS quantum dots and pure ZnO nanoparticles with different experimental conditions. Treatment with sodium hydroxide as a capping agent is investigated systematically during the synthesis of ZnS quantum dots (QDs). The thickness of the ZnS shell is controlled by the concentration of the sodium sulphide during the synthesis of ZnO–ZnS core–shell nanostructures. The morphology and structure of samples are verified by X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM) and energy dispersive X-ray analysis (EDX). The UV–vis absorption spectra of the pure ZnS QDs exhibit a blue shift in the absorption edge due to the quantum confinement effect. The PL emission spectra of the ZnO–ZnS core–shell nanostructure are compared with the ZnO nanoparticles. The ZnO–ZnS core–shell nanostructures show decrease in the UV and green emissions with the appearance of a blue emission, which are not found in the ZnO nanoparticles.